Clinical practice: Surfactants and their role in biofilm management in chronic wounds. Issue 1 (2019) - Tyldesley, Heather Charlotte; Salisbury, Anne-Marie; Chen, Rui; Mullin, Marc; Percival, Steven L.
No abstract available